Computational fluid dynamic modelling of FCC riser: A review - Shah, Milin; Utikar, Ranjeet; Pareek, Vishnu; Evans, G.; Joshi, J. (Elsevier, 2016)
Design and scale-up of fluid catalytic cracking (FCC) riser is still largely empirical, owing to limited understanding of inherent multiphase flow in this equipment. The multiphase flow of FCC riser has therefore been extensively investigated both experimentally and computationally. The experiments have provided significant insight into gas-solid flow patterns inside cold-flow risers, but simultaneous observations on flow and performance parameters (conversion and yields) in FCC riser are rarely found in literature. Consequently, computational fluid dynamic (CFD) models of FCC riser that can simultaneously account for flow, interphase interactions, droplet vaporization and cracking kinetics have been developed. The CFD modelling of FCC riser, despite several efforts, has still remained a challenge as it requires careful consideration of governing equations and closure models. This review presents state-of-the-art in CFD modelling and experimental analysis of gas-solid hydrodynamics and reactive flow of FCC riser. The CFD models are explained in greater detail with governing equations, constitutive relations, and physical significance of all the terms. A brief review of DNS studies on cluster formation, gas-solid drag, and turbulent interactions is also presented. Impact of important closure models such as drag models, viscous stress models, boundary conditions, droplet vaporization models, and kinetic models on predictions is critically examined. The review identifies major shortcomings of current CFD models and makes detailed recommendations for future work.